Temporarily quadrupling the dose of inhaled steroid to prevent asthma exacerbations: FAST - McKeever, T; Mortimer, K; Bradshaw, L; Haydock, R; Pavord, I; Higgins, B; Walker, S; Wilson, A; Price, D; Thomas, M; Devereux, G; Brightling, C; et al. (NIHR Journals Library, 2018)
Background Asthma exacerbations affect the quality of life of patients with asthma and have a major effect on the overall costs of asthma care. An asthma self-management plan that advises the temporary quadrupling of inhaled corticosteroid dose may prevent asthma exacerbations, but this needs to be confirmed before being adopted widely. Objectives To compare the clinical effectiveness and cost-effectiveness of an asthma self-management plan that advises patients to temporarily quadruple the dose of inhaled corticosteroid when asthma control starts to deteriorate with a standard self-management plan. Design A multicentre, parallel-group, pragmatic randomised trial, with follow-up for 12 months. Setting Primary and secondary care across 207 sites in the UK. Participants Asthma patients aged ≥ 16 years treated with an inhaled corticosteroid who had experienced at least one exacerbation in the previous 12 months. Interventions Participants were randomised (1 : 1) to a usual-care self-management plan or to a modified self-management plan that advised a temporary quadrupling of the inhaled corticosteroid at the point of asthma deterioration, both of which were actively implemented and supported by local research staff. Primary outcome The primary outcome of ‘time to first asthma exacerbation’ was defined as the need for systemic corticosteroids (for at least 3 consecutive days) and/or unscheduled health-care consultations for asthma (i.e. reaching zone 3 or 4 of the Asthma UK self-management plan). Results A total of 1922 participants were randomised: the primary analysis included 938 participants (97%) in the usual-care group and 933 participants (97%) in the modified self-management group. The number of participants having at least one exacerbation of asthma in the year after randomisation was 484 (51.6%) in the usual-care group and 420 (45.0%) in the modified self-management group [adjusted hazard ratio 0.81, 95% confidence interval (CI) 0.71 to 0.92; p = 0.002]. There were fewer serious adverse events reported in the modified self-management group than in the usual-care group (11 vs. 32, respectively). Eight and six events of pneumonia, lower respiratory tract infections or influenza were reported in the usual-care group and the modified self-management group, respectively. Health-care-related costs were lower in the modified self-management group. The modified self-management group was £24 (bootstrapped 95% CI –£122 to £71) less costly than usual care, with a greater quality-adjusted life-year gain of 0.02 (bootstrapped 95% CI –0.005 to 0.04). Therefore, the modified self-management group was ‘dominant’, with a 94–95% probability of being cost-effective at the £20,000–30,000 threshold. Limitations As the Fourfold Asthma STudy (FAST) was an open-label pragmatic trial, the possibility of treatment bias that may have affected the participants in the modified self-management group cannot be ruled out. Poorer than expected completion of participant diary cards, particularly within the usual-care self-management group, could have led to a null bias, underestimating the true effect of the intervention. Conclusions An asthma self-management plan that advises patients to temporarily quadruple their dose of inhaled corticosteroid at the point of asthma symptoms worsening does reduce clinically important asthma exacerbations. In addition, the plan is cost-effective compared with the usual-care self-management plan. Future work To effectively implement asthma self-management plans that advise a temporary quadrupling of inhaled steroid at asthma deterioration into routine practice.